2016
DOI: 10.1287/mksc.2015.0952
|View full text |Cite
|
Sign up to set email alerts
|

Price Reactions to Rivals’ Local Channel Exits

Abstract: I n this paper, we study the effect of a firm's local channel exits on prices charged by incumbents remaining in the marketplace. Exits could result in higher prices due to tempered competition or lower prices due to reduced colocation or agglomeration benefits. The net effect of these two countervailing forces remains unknown. In addition, little is known about how this effect could change depending on incumbents' geographic locations. We address this research gap by examining new car price reactions by incum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Furthermore, our work informs the debate on the agglomeration effects of dealer co‐location (Benmelech et al. 2019, Murry and Zhou 2019, Ozturk, Venkataraman, and Chintagunta 2016). The basic theoretical models recommend avoiding co‐location to reduce competition (Baum and Haveman 1997).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, our work informs the debate on the agglomeration effects of dealer co‐location (Benmelech et al. 2019, Murry and Zhou 2019, Ozturk, Venkataraman, and Chintagunta 2016). The basic theoretical models recommend avoiding co‐location to reduce competition (Baum and Haveman 1997).…”
Section: Discussionsupporting
confidence: 64%
“…Second, we add to the literature that focuses on a firm's ex post strategic responses to a rival's bankruptcy to recognize the effects of ex ante investments. Such literature has shown that firms respond to a rival's bankruptcy by changing their product variety (Ren et al, 2019) and prices (Ozturk et al, 2016). Further, their sales can be affected by a rival's crisis (e.g., Giannetti & Srinivasan, 2021;Ozturk et al, 2019).…”
Section: Implications For Theory and Practicementioning
confidence: 99%
“…Second, when a firm files for bankruptcy, it has the potential to generate widespread spillovers to other firms in the industry. Research shows that one firm's bankruptcy can affect the sales and prices of other firms in the industry (Ozturk et al, 2016(Ozturk et al, , 2019. Research also shows that bankruptcy can affect the stock returns for other firms in the industry, and business examples are prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have primarily focused on the influence of supply chain structures on the competitive actions of firms. Recent papers in this literature have investigated the impact of several supply chain structures on outcomes such as innovative output (Bellamy et al 2014), firms' financial performance (e.g., Wang et al 2021), retail prices (Ozturk et al 2016), and retail sales (Osadchiy et al 2016).…”
Section: Ozturk and Tereyagoglu: Multimarket Distribution Relationshipsmentioning
confidence: 99%